Can Fixing Dinner Fix the Planet? - Fanzo, Jessica (Johns Hopkins University Press, 2021)
How can consumers, nations, and international organizations work together to improve food systems before our planet loses its ability to sustain itself and its people?Do we have the right to eat wrongly?As the world's agricultural, environmental, and nutritional needs intersect-and often collide-how can consumers, nations, and international organizations work together to reverse the damage by changing how we make, distribute, and purchase food? Can such changes in practice and policy reverse the trajectories of the biggest global crises impacting our world: the burden of chronic diseases, the consequences of climate change, and the systemic economic and social inequities that exist within and among nations?Can Fixing Dinner Fix the Planet? is a clarion call for both individual consumers and those who shape our planet's food and environmental policies that:• describes the often destructive path that foods take from farms and seas through their processing, distribution, marketing, purchasing and waste management sites• explores the complex web of factors impacting our ability to simultaneously meet nutritional needs, sustain biodiversity and protect the environment• raises readers' food and environmental literacy through an engaging narrative about Fanzo's research on five continents along with the work of other inspiring global experts who are providing solutions to these crises• empowers readers to contribute to immediate and long-term changes by informing their decisions in restaurants, grocery stores, farmers markets, and kitchens